1995
DOI: 10.1111/j.1432-1033.1995.513_b.x
|View full text |Cite
|
Sign up to set email alerts
|

Receptor‐Mediated Regulation of Leukotriene C4 Synthase Activity in Human Platelets

Abstract: Human platelets possess a specific membrane-bound leukotricnc (LT) C., synlhase, which catalyzes the conversion of LTA, to LTC,. Sti tnulation of the rcccptoi-s for thronibin, collagen or thromboxane A, provoked inhibition of this cnzyme, as judged by suppressed trmsformation of exogenous LTA, to LTC,.Similarly, direct activation of protein kinase (PK) C with riiltiomolur concentrations of 4/1-phorhol 12-myristate 13-acelate (PMA) inhibited the production of I,TC:,. Kinetic studies demonstrated that the i nhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Nevertheless, the amounts of LTC 4 produced from LTA4 in the presence of catalase were almost 50% of LTB4 levels in intact cells and similar to those of LTB 4 in disrupted granulocytes, demonstrating considerable LTC4-producing capacity within the granulocyte preparation. The possibility that contaminating platelets contributed substantially to this capacity can be excluded, since the conversion of LTA4 to LTC4 in granulocyte suspensions was unaffected by the thromboxane analogue U-46619 (Sj61inder et al, unpublished observation), which induce down-regulation of LTC4 synthase activity in platelets [23]. Furthermore, the number of remaining platelets in the granulocyte suspensions was always low (see section 2).…”
Section: -Omentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the amounts of LTC 4 produced from LTA4 in the presence of catalase were almost 50% of LTB4 levels in intact cells and similar to those of LTB 4 in disrupted granulocytes, demonstrating considerable LTC4-producing capacity within the granulocyte preparation. The possibility that contaminating platelets contributed substantially to this capacity can be excluded, since the conversion of LTA4 to LTC4 in granulocyte suspensions was unaffected by the thromboxane analogue U-46619 (Sj61inder et al, unpublished observation), which induce down-regulation of LTC4 synthase activity in platelets [23]. Furthermore, the number of remaining platelets in the granulocyte suspensions was always low (see section 2).…”
Section: -Omentioning
confidence: 99%
“…However, although direct activation of PKC induced attenuation of platelet LTC 4 synthase activity, receptormediated regulation of the enzyme appeared to be primarily dependent on the function of another protein kinase, possibly a tyrosine specific kinase [23]. Therefore, further investigation of possible receptor-mediated LTC 4 synthase regulation in myeloid cells is warrented.…”
Section: -Omentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that TBXA2 can be considered a negative regulator of LTC 4 synthase activity, which is responsible for leukotriene production, and have also suggested that when TBXA2 formation is prevented, LTC 4 synthase activity is elevated, leading to increased biosynthesis of leukotriene and clinical symptoms [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%